(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
Textbooks are standard media that teachers and students must have. Books also cannot provide moving material (animation) and lack the use of attractive colors. With the development of technology, students are accustomed to using smartphones, which include a variety of games, animations and other interesting interactive applications. The use of applications really attracts students’ interest in using them so that if given the opportunity to use smartphones in learning activities compared to books. Students are very enthusiastic because there are interactive animations in the material on their smartphones. The teachers also saw that this phenomenon could be used to increase students’ interest in learning, so the teachers felt the need to create material in the form of animated applications that could be interacted with. With the existing problems, it is felt that this training is very necessary to train teachers in creating learning animation applications that cover material topics for students. This training can also increase teacher competency. From this training, the teacher will create and produce a learning animation application for students. This training begins with a presentation and simulation, after which the teachers create applications either in groups or individually. The resulting application is then tested. The application created can increase students’ interest in learning and make it easier for students to study anywhere and anytime with the help of a smartphone.